Implikasi Putusan Itsbat Nikah yang Melanggar Prinsip Ultra Petita (Analisis Perkara Nomor 282/PDT.G/2020/PA.BJB JO. 40/PDT.G/2020/PTA.BJM) - Siregar, Mahyuni Ayu (Wajah Hukum, 2026)
Unregistered polygamy which occurred prior to the enactment of 1974 Indonesian Marriage Law raises legal problems when inheritance disputes arise. This article mainly analyzes the problem on Case 282/Pdt.G/2020/PA.Bjb alongside with 40/Pdt.G/2020/PTA.Bjm. There are two main questions addressed in this article: (1) how the judges consider the law in determining the judicial confirmation of the marriage, and; (2) implications of the courts’ ruling on the temporal limit of the marriages towards the legal status of the children. The research on this article is done in using doctrinal legal research, using a case approach. The analysis shows that the Court has exceeded the scope of the petition (ultra petita) by setting a temporal boundary on the first marriages. This has direct implications towards the legal status of children born after that temporal limit. Accordingly, it is needed to apply maqashid syariah and progressive legal approach on deciding juridical confirmation cases.